MECHANISMS FOR IMPROVING THE SOCIAL MOBILITY OF WOMEN IN THE MODERNIZATION OF SOCIETY (Scientific journal of the Fergana State University, 2024)
In this article, the author analyzed and described the mechanisms for increasing the social mobility of women in Uzbekistan, in the conditions of modernization of society. Our country has created modern conditions and opportunities for the education and employment of women in various spheres of public life, with special attention being paid to the meaningful organization of their free time.